2017
DOI: 10.3389/fimmu.2016.00697
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Autoimmunity: Molecular Mechanisms and Therapeutic Potential

Abstract: Over the last three decades, it has become clear that the role of vitamin D goes beyond the regulation of calcium homeostasis and bone health. An important extraskeletal effect of vitamin D is the modulation of the immune system. In the context of autoimmune diseases, this is illustrated by correlations of vitamin D status and genetic polymorphisms in the vitamin D receptor with the incidence and severity of the disease. These correlations warrant investigation into the potential use of vitamin D in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
267
2
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(291 citation statements)
references
References 249 publications
(313 reference statements)
6
267
2
16
Order By: Relevance
“…34,47 This study showed that a rather high proportion of RPL patients have vitamin D deficiency compared with women with NP, consistent with previous studies. 34,47 This study showed that a rather high proportion of RPL patients have vitamin D deficiency compared with women with NP, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…34,47 This study showed that a rather high proportion of RPL patients have vitamin D deficiency compared with women with NP, consistent with previous studies. 34,47 This study showed that a rather high proportion of RPL patients have vitamin D deficiency compared with women with NP, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The immunomodulatory function of vitamin D in immune-related diseases has garnered increasing attention, including in the case of maternal fetal immune imbalance diseases, which contribute to RPL. 34,47 This study showed that a rather high proportion of RPL patients have vitamin D deficiency compared with women with NP, consistent with previous studies. 44,48,49 A prospective cohort study of 1191 women showed an association between sufficient preconception levels of 25(OH)D 3 (≥75 nmol/L) and increased rate of pregnancy and live birth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Vitamin D supplementation is generally used as a preventive agent or a co-adjuvant for diseases with underlying autoimmune or pro-inflammatory states (Bscheider and Butcher, 2016;Dankers et al, 2017). DCs represent an excellent target of vitamin D to dampen autoimmunity and inflammation, not only because these myeloid cells express the whole set of enzymes to generate the active form of vitamin D (Mora et al, 2008) but also for their unique role as initiators of immune responses.…”
Section: Introductionmentioning
confidence: 99%